The Influence of Matrix Shape and Resin Composition on Tensile and Bending Strength - Zufar Jamaluddin; Yatin Ngadiyono; Arif Marwanto (Program Studi Sarjana Terapan Teknik Mesin, Fakultas Vokasi, Universitas Negeri Yogyakarta, 2025)
This study aims to determine the differences in tensile and bending strength caused by the use of 45° and 0° fiber orientations, to identify the ideal resin and catalyst composition, and to explain the mismatch between direct testing and ANSYS simulation results. The research used an experimental method. The specimen manufacturing process included preparation of tools and materials, mold preparation, resin-catalyst mixing, fiber preparation, vacuum infusion, cutting, and sanding. The specimens were manufactured using hand lay-up and vacuum infusion by arranging fibers on the mold and applying vacuum pressure at the end of the fabrication process. The results show that carbon composite laminates with 0° fiber orientation provide greater tensile and bending strength than those with 45° fiber orientation. The carbon composite had the highest tensile load when the resin and catalyst composition was 4:1, while the highest bending load was obtained for the 3:1 resin and catalyst composition. The difference between simulation and direct testing was caused by the assumption in ANSYS that the fiber-matrix bonding was perfect, while in actual specimens the resin distribution and bonding varied due to the vacuum infusion process.